The island of forgotten gods - Piñeiro, Victor (Sourcebooks Young Readers, an imprint of Sourcebooks Kids, 2025)
Twelve-year-old Nico and his cousins' seemly boring summer in Puerto Rico takes a horrific turn when they encounter the legendary chupacabra, a cult, and the gods who created the island.